IMPLEMENTASI PERATURAN BUPATI PAMEKASAN NOMOR 2 TAHUN 2022 TENTANG KAWASAN TANPA ROKOK DI RSUD WARU KABUPATEN PAMEKASAN - Erina Saputri; R. Sonia Rizqia Zidkin; Mohammad Bustanol Husein (Journal Publicuho, 2024)
Pamekasan is one of the tobacco producing districts in Indonesia. The high death rate and the impact caused by smoking are the initial steps of the Pamekasan Regency government to create regulations through Pamekasan Regent Regulation Number 2 of 2022 concerning Smoke-Free Areas. One of the policies that has been implemented is Waru Regional Hospital. The theory used in this study is the theory of George C. Edward III (1980) in which there are 4 interrelated variables, namely Communication, Resources, Disposition or Attitude of Implementers and Bureaucratic Structure. The type of research used is research with a descriptive approach as the basis for analyzing the implementation of smoke-free areas at Waru Regional Hospital, Pamekasan Regency. The results of the study show that the Implementation of Pamekasan Regent Regulation Number 2 of 2022 concerning Smoke-Free Areas at Waru Regional Hospital, Pamekasan Regency has not gone well and optimally because of the 4 indicators from George C. Edward III's theory that only 1 indicator has been fulfilled, namely in the Disposition or Attitude of Implementers aspect, while the other indicators are not optimal.